Trading for a living : psychology, trading tactics, money management - Elder, Alexander, Dr. (John Wiley and Sons, 1993)
Individual psychology. Mass psychology. Classical chart analysis. Computerized technical analysis. The neglected essentials. Stock market indicators. Psychological indicators...